(untitled) (PerCursos, 2021)
The current discussion has as mandatory reference Walter Benjamin as the Narrator and the oral narratives that collaborate in constructing Xukuru-Kariri indigenous people’s territory in Palmeira dos Índios (AL). Benjamin seeks the value in the history that orally lives to rescue the alterity’s importance in the ethics constitution process, seeking the real place that the human being must occupy in a historical period characterized by the growing valorization of relations founded on the alienation and reification of individuals. The exercise of cultivating the memory among the traditional people aggregates mainly the function of educating, besides agglutinating information, experiences, past times which when rummaged gave origin to the recuperation of the old territory (once occupied), also used in the exercises from everyday tasks, from funeral rituals, from runaways from invaders, from drought, from hunger. Talking in a historical narrative and memory of the forgotten is the invocation of a past, which one cannot retake in its totality; it is to appeal to the meetup face to face with the other, which constitutes itself as the eminently distinct being of the Self. It is the resurgence of the historical narrative and the forgotten is memory, which passes necessarily by hearing the past presented by the other. Throughout this text, we will present this Other’s face, forgotten in the context of a society that values the present time and the cartesian Self solely.